Abacada boosting the Abaca industry through a research, development, and livelihood training facility - Jasme, Mhel Markin Jo W. (College of Architecture, University of the Philippines Diliman, 2019)
The Philippine abaca industry has been a growing industry ever since it received its popularity not only nationwide but also in some countries worldwide. Exports are done in countries such as the United States, United Kingdom, Japan, India, China, South Korea, Australia, and a lot more. The uses of abaca include the making of craft products, twines, ropes, nets, fishing lines, cordage, and furniture. It is also eyed as alternatives for non-biodegradable materials, and as composite materials in automotive and aeronautics fields. However, despite these growing demand, popularity, and potentials, there are still issues and problems encountered within the value chain of the abaca industry. The value chain has three phases - production, processing, and marketing & trading. In the production phase, there have been reports on the infestation of viruses and diseases, conversion of abaca plantations to other crops, lack of support and planting materials, and insufficient capital for farmers. The processing phase also encountered issues such as lack of equipment and proper training. Lastly, in marketing and trading, issues such as lack of marketing structure and access to traders and exporters are encountered. In consideration with the problems identified, the researcher came up with a goal which is to provide enhanced avenues for research, learning/training, quality production, awareness, and appreciation in the abaca industry through a more developed, conducive, and technologically-advanced research, development, and training facility.